DNA binding of heat shock factor to the heat shock element is insufficient for transcriptional activation in murine erythroleukemia cells. - Hensold, J O (1990)
The heat shock response is among the most highly conserved examples of regulated gene expression, being present in all cellular organisms. Transcriptional activation of heat shock genes by increased temperature or other cellular stresses is mediated by the binding of a heat shock factor (HSF) to a conserved nucleotide sequence (the heat shock element) present in the promoter of heat-inducible genes. Despite the high degree of conservation of this response, embryonic stages of development are characterized by the absence of a heat shock response. Murine erythroleukemia (MEL) cells also lack this response, and we report here a detailed characterization of this defect for one of the most highly conserved of these genes, hsp70. Surprisingly, heat-induced transcriptional activation of this gene does not occur, despite the induction of a protein with the binding specificity of murine HSF. However, the MEL HSF differs slightly in apparent size from the HSF in 3T3 cells, which exhibit a normal heat shock response. These data suggest that activation of mammalian HSF by heat requires at least two separate steps: an alteration of binding activity followed by further modification that activates transcription. MEL cells do not respond to heat shock because they lack the ability to perform this secondary modification. These cells provide a useful system for characterizing heat shock activation in mammals.